La transferencia léxica en la comprensión auditiva en los aprendices de portugués hablantes de español - Rocío Alonso Rey, María (Revista Vozes dos Vales: Publicações Acadêmicas, 2025)
This paper examines lexical transfer as L1-influence mechanism different from interference and presents the results of a comprehension test performed by Spanish speakers learners of Portuguese. The results show evidence of transfer as cross-linguistic association in comprehension and confirms the undifferentiated perception as a specific feature in this learners acquisition. Finally, some pedagogical implications are exposed.